НЕКОТОРЫЕ РЕЗУЛЬТАТЫ СПЕКТРАЛЬНОГО АНАЛИЗА ВРЕМЕННЫХ РЯДОВ НАБЛЮДЕНИЙ МОРСКИХ БИОСИСТЕМ - (:unkn) unknown (Киев : Наукова думка, 1981)
С помощью спектрального математического анализа установлено, что на высоких частотах, периода колебаний (10—30 сут), освещенность обусловливает изменение численности диатомовых водорослей сообществ микроорганизмов планктона, перифитона и взвеси в море. Выявлены корреляции этих и других параметров изучаемой биосистемы.
Certain results of spectral analysis of time series in observations of a sea biosystem
Spectral mathematical analysis made it possible to establish that at high frequencies (the period of observations 10-30 days) mainly illumination causes changes in the quantity of Diatoms in the microorganism communities of plankton, periphyton and suspension in the sea. Correlations of these and some other parameters of the biosystem under study are detected.